2022
DOI: 10.1002/cam4.4828
|View full text |Cite
|
Sign up to set email alerts
|

Advances in exosome biomarkers for cervical cancer

Abstract: Cervical cancer (CC) ranks as the fourth most frequently diagnosed malignancy in females worldwide. Exosomes are a subclass of extracellular vesicles released by nearly all types of cells that act as cargo transport vehicles, carrying proteins, and genetic material (such as miRNAs, long noncoding RNAs, and mRNAs) derived from their parent cells may affect receiving cells and thus have emerged as key players in several biological processes, including inflammatory pathways. In this review, we concentrated on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 157 publications
0
1
0
Order By: Relevance
“…Because there are few validated biomarkers, we are often unable to predict treatment effects for CC. Previous studies have shown that CC biomarkers, including exosomes ( Ran et al, 2022 ), microRNAs ( Laengsri et al, 2018 ), and DNA and RNA molecules ( Volkova et al, 2021 ) are associated with CC diagnosis, therapy, and prognosis. Nevertheless, the lack of reported evidence indicates that the inflammatory response-related gene signature has not been established as a prognostic marker for CC.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are few validated biomarkers, we are often unable to predict treatment effects for CC. Previous studies have shown that CC biomarkers, including exosomes ( Ran et al, 2022 ), microRNAs ( Laengsri et al, 2018 ), and DNA and RNA molecules ( Volkova et al, 2021 ) are associated with CC diagnosis, therapy, and prognosis. Nevertheless, the lack of reported evidence indicates that the inflammatory response-related gene signature has not been established as a prognostic marker for CC.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for differentiating between various types of cancers using exosomal biomarkers is a key area of investigation, aiming to establish panels of biomarkers for improved diagnostic accuracy [ 135 ]. Additionally, investigations into the prognostic value of exosomal biomarkers connect specific exosome profiles to disease progression and prognosis, guiding treatment strategies and informing patients about the likely course of their cancer [ 136 , 137 , 138 , 139 ]. Research efforts have expanded to explore the clinical utility of exosomal biomarkers across various cancer types, enhancing the applicability of exosome-based diagnostics [ 136 , 140 ].…”
Section: Clinical Trials On Extracellular Vesiclesmentioning
confidence: 99%
“…Cervical cancer (CC) ranks as the fourth most common cancer among women and is a leading cause of cancer-specific mortality among women worldwide ( Rahangdale et al, 2022 , Ran et al, 2022 ). In 2020, 604,000 new CC cases were diagnosed, and resulted in 342,000 deaths in women globally ( Poniewierza and Panek, 2022 ).…”
Section: Introductionmentioning
confidence: 99%